2018
DOI: 10.1053/j.jfas.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

A Perifascial Areolar Tissue Graft With Topical Administration of Basic Fibroblast Growth Factor for Treatment of Complex Wounds With Exposed Tendons and/or Bones

Abstract: The management of wounds with tendon and/or bone exposure is challenging because of the insufficient blood supply to the wound bed. We describe our experience with 19 patients using a perifascial areolar tissue (PAT) graft with topical administration of basic fibroblast growth factor (bFGF) in the treatment of complex wounds with exposed tendons and/or bones in the extremities. Using a PAT graft is minimally invasive and technically easy, and the donor site is relatively preserved. However, PAT grafts for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Previous clinical studies have speculated that the survival of PAT grafts is facilitated by capillary anastomosis between the capillaries in the PAT and those in the recipient wound bed [ 3 , 5 , 6 ]. However, no studies have provided definitive evidence of vascular bridging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have speculated that the survival of PAT grafts is facilitated by capillary anastomosis between the capillaries in the PAT and those in the recipient wound bed [ 3 , 5 , 6 ]. However, no studies have provided definitive evidence of vascular bridging.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PAT may serve as a high-quality graft tissue for wounds involving the exposed ischemic tissue and any membrane structure. Despite the success of PAT grafts in clinical case studies, fundamental research on their molecular composition and ability to promote wound healing in ischemic structures is lacking [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…of perifascial areolar tissue (PAT) grafts for exposed bone wounds is an ideal option as it is minimally invasive, is technically easy, and requires less donor site sacrifice. However, PAT grafts for the treatment of complex wounds with large areas of exposed bone sometimes fail to survive because of insufficient vascularization to the grafted tissue 3,4) . Hayashi et al evaluated the results of 13 PAT grafts used to cover narrow ulcers with tendon-or bone-exposed areas and concluded that covering exposed cortical bone ulcers may be difficult with this technique, and that PAT grafting is not suitable for tendon exposure with a width > 2 cm 5) .…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of this technique has been shown in several reports. 3 4 5 6 7 8 However, all of these were clinical reports, and the size and depth of the wound, the exposed tissue, the presence or absence of surrounding blood flow, the presence or absence of irradiation, the site of the wound, and so forth are diverse. The appropriate surgical indications are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is a loose connective tissue and part of a group of structures known as the lubricant adipofascial system reported by Nakajima et al 9 Since the PAT has a layered structure of the delicate network of thin collagen fibers, it is possible to harvest supple and thin tissue. 3 In clinical cases, the PAT is often harvested from the inguinal region or the outside of the thigh in consideration of the cosmetic result and invasiveness. 4 In this model, the PAT was harvested from the back of the rat.…”
Section: Discussionmentioning
confidence: 99%